HUBUNGAN PERAN PENYULUHAN TERHADAP TINGKAT KEBERDAYAAN PETANI SAGU DI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Ade Tri Irawan; Rosnita Rosnita; Roza Yulida (Fakultas Pertanian, Universitas Riau, 2020)
The purpose of this research is: 1) Analyze the role of agricultural extension that has been carried out by extension worker in sago farming activities in Tebing Tinggi Barat Sub-district of Kepulauan Meranti Regency, 2) Analyze the level of sago farmers empowerment in Tebing Tinggi Barat Sub-district of Kepulauan Meranti Regency, 3) Analyze the relationship of agriculture extension with the level of sago farmers empowerment in Tebing Tinggi Barat Sub-district of Kepulauan Meranti Regency. This research used survey method. Research do in Tebing Tinggi Barat Sub-district of Kepulauan Meranti Regency starts from February 2017 to January 2018. Respondents as many as 70 sago farmers has taken in Purposive Sampling. The data analysis be used is Likert Scale and Spearman's Rank Correlation. The result of research shown that: 1) Agricultural extension conducted by extension workers in Tebing Tinggi Barat Sub-district of Kepulauan Meranti Regency belong to the category of